Identification of the Factors of Sustainable Development of Regional Agricultural Systems Using Regression Model - Pavlov, Alexander Yu.; Karmyshova, Julia V. (International Journal of Economics and Financial Issues, 2015)
The study is aimed at providing a theoretical basis for the relevance of sustainable development of regional agricultural systems and the development of practical recommendations for the implementation of the algorithm evaluation of the factors affecting the condition of agricultural production at the regional level. The study uses a systematic approach, supplemented with multifunctionality paradigm of agricultural production, which has enabled to develop an algorithm that includes a series of steps aimed at creating a regression model that reflects the significance of selected factors and their impact on the development of regional agricultural system. The developed method is tested in a study of rural areas of the Penza region, situated in the Central European part of Russia. The proposed indicators of sustainable development of regional agricultural systems are able to objectify the process of further evaluation of the spatial inhomogeneity of the factors determining sustainability of the agricultural production. The research findings provide additional opportunities in the agricultural development of the region. Keywords: sustainable development factors, agricultural system, rural areas, regional development, regression model JEL Classifications: 013, R11